Uncovering the dynamics of interaction in development cooperation: A review of the "new actors in development" research agenda - Adam Moe Fejerskov; Erik Lundsgaarde; Signe Marie Cold-Ravnkilde (Danish Institute for International Studies (DIIS), 2016)
The rising prominence of new state and non-state actors in international politics has stimulated extensive discussion in the social sciences over the last decade and development cooperation has been a central arena for conceptualising the encounter between old and new powers. This working paper critically reflects on the substantial body of scholarship that seeks to document the characteristics of new actors in international development and chart the consequences of their engagement for global development governance. This review underlines the importance of questioning the homogeneity of actor constellations, relationships and ideas. Specifically, it addresses the extent to which the commonly-used binary concepts of development cooperation provider groups adequately capture relevant distinctions among the actors and add analytical value to research on development cooperation. The paper advocates adopting more analytically and conceptually diverse approaches to study the interaction between heterogeneous development actors and homogenising forces in the field of development cooperation, recognising the complexity and (dis)continuities of stability and change in this arena.
Keywords: 330